2013
DOI: 10.1177/0363546512472441
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Based Topographical Differences Between Control and Recurrent Patellofemoral Instability Patients

Abstract: The MRI-based patellar tilt measures proved to be an excellent group of measurements for delineating between controls and those with instability. Patella alta ratios, such as Insall-Salvati and Caton-Deschamps, demonstrated a statistically significant difference between normal and recurrent dislocators. Trochlear measurements proved significantly different at the proximal and distal trochlea. Our findings demonstrate that MRI is appropriate to help discern recognized pathologic abnormalities that characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(168 citation statements)
references
References 36 publications
7
156
0
2
Order By: Relevance
“…TD was calculated on axial scans on both CT and MRI as the perpendicular distance between the deepest point on the trochlear sulcus and the line joining the superior point of medial and lateral trochlear facets facet (seven had low-grade and five had high-grade cartilage defect)(Figs. 5,6). No other association was found between any other qualitative and quantitative variables.…”
mentioning
confidence: 81%
“…TD was calculated on axial scans on both CT and MRI as the perpendicular distance between the deepest point on the trochlear sulcus and the line joining the superior point of medial and lateral trochlear facets facet (seven had low-grade and five had high-grade cartilage defect)(Figs. 5,6). No other association was found between any other qualitative and quantitative variables.…”
mentioning
confidence: 81%
“…They found the sulcus angle and the trochlear index, defined as the sum of the height of the condyles divided by the height of the sulcus, being the most reliable measurements. In our study we used the medial-to-lateral facet ratio, as MRI studies in adults confirmed a higher risk of femoro-patellar instability in higher ratio of the lateral-to-medial facet [12,13]. The average ratio we determined in our study was 1.31, which corresponds to the expected non-dysplastic population.…”
Section: Discussionmentioning
confidence: 72%
“…The criticism of this measurement as a gold standard is that it does not account for the variance of patella shape. 24 Images with progressive flexion can be very useful to verify reduction of lateral patellar tilt. The lack of reduction during early flexion suggests lateral tightness.…”
Section: Imagingmentioning
confidence: 99%